Pemberdayaan ibu-ibu kelompok binaan PKK melalui pelatihan dan pendampingan kreasi toples hias dari limbah perca kain - Irmayanti Irmayanti; Hamidah Suryani; Sukriati Firman (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Empowerment of family welfare program women as members of the community and still classified as productive workers is very important. The goal is not only to foster awareness and independence but also to expand employment opportunities to increase family income as an effort to achieve a happy and prosperous family. Utilization of patchwork waste which is the leftovers from the production both from the textile industry and the fashion industry can provide new jobs for the community, especially in the case of family welfare program women. The methods used were: lecture, demonstration and question and answer. The results achieved were: (1) partners have the knowledge and skills in making handicrafts like decorative jars from patchwork waste, (2) partners are able to fill their free time with the skills to make crafts like decorative jars from patchwork waste, ( 3) partners already have knowledge about how to make handicrafts like decorative jars from patchwork waste and apply that knowledge and skills to increase family income, (4) the final results of partner work can be categorized as quite neatly although training is still needed to further reinforce and enhance creativity